Air Quality Monitoring System Development using IoT for Indoor Applications - Acharya K., Aneessha; V. Kolekar, Sucheta (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The third sustainable goal defined by the United Nations is about good health and well-being, in which air quality is a major concern in today’s environment. The presence of harmful, if not noxious gases, degrades the quality of air present in our surroundings. The presence of this particulate matter affects the overall health of many individuals. Especially with the rise of COVID-19 and its variants in recent years, even breathing normally may become an arduous task for an individual. The pollutants in the air may facilitate worsening conditions for an affected individual. Hence, the present work aims to develop an indoor air quality monitoring system that alerts the user when the air quality worsens into harmful ranges such as good, moderate, and unhealthy. The present work utilizes multiple sensors to take readings of different environmental pollutants multiple times a day. These readings are uploaded to a cloud database. A mobile application was made to view these readings. The mobile application interfaces with the cloud database and gets the latest sensor data, which is viewable on the main screen. The application also visualizes the data collected in the past 24 hours. The readings for each day were aggregated, and the average was taken to be converted into an AQI index based on the US EPA standard. This was then compared against AQI data for the day provided by the Delhi Pollution Control Committee. The readings were in a suitable accuracy range for the present work, thus validating the monitoring system design. The analysis and alert time were considered for validating the application design and data analysis.